Isometric skeletal muscle contractile properties in common strains of male laboratory mice - Minchew, Everett C.; Williamson, Nicholas C.; Readyoff, Andrew T.; McClung, Joseph M.; Spangenburg, Espen E. (Frontiers in Physiology, 2022)
Assessing contractile function of skeletal muscle in murine models is a commonly employed laboratory technique that investigators utilize to measure the impact of genetic manipulations, drug efficacy, or other therapeutic interventions. Often overlooked is the potential for the strain of the mouse to influence the functional properties of the skeletal muscle. Thus, we sought to characterize commonly assessed isometric force measures in the hindlimb muscles across a variety of mouse strains. Using 6-8-week-old male mice, we measured isometric force, fatigue susceptibility, contractile kinetics, muscle mass, myofiber cross-sectional area, and fiber type composition of the extensor digitorum longus (EDL) and soleus muscles in C57BL/6NJ, BALB/cJ, FVB/NJ, C57BL/6J, and C57BL/10 mice. The data demonstrate both unique differences and a number of similarities between both muscles in the various genetic backgrounds of mice. Soleus muscle specific force (i.e., force per unit size) exhibited higher variation across strains while specific force of the EDL muscle exhibited minimal variation. In contrast, absolute force differed only in a few mouse strains whereas analysis of muscle morphology revealed many distinctions when compared across all the groups. Collectively, the data suggest that the strain of the mouse can potentially influence the measured biological outcome and may possibly promote a synergistic effect with any genetic manipulation or therapeutic intervention. Thus, it is critical for the investigator to carefully consider the genetic background of the mouse used in the experimental design and precisely document the strain of mouse employed during publication.